Preliminary report on the living non-marine Ostracoda (Crustacea) from Tunisia with the description of a new Psychrodromus species - Zaibi, Chahira; Scharf, Burkhard; Viehberg, Finn Andreas; Keyser, Dietmar; Kamoun, Fekri (Zootaxa, 2013)
Since 1928, Henri Gauthier has been the only zoologist to describe the extant non-marine ostracod fauna of Tunisia. In 2010, new samples of living non-marine ostracods were collected from central and southern Tunisia. A complete list of the 41 non-marine ostracods of Tunisiais presented, including the species of Gauthier’s work, published Holocene records, and new results from our field study. Historical faunal variations (El Melah Lagoon, Lac de Tunis, Sebkhas El- Guettiate and Dreîaa, and Lac Ichkeul) are briefly discussed and related to recent environmental changes. In 2006, El Melah Lagoon contained a freshwater, brackish, and a marine ostracod assemblage. In the future, this lagoon will probably dry up and become a sebkha. Lac de Tunis has developed from a marine bay over a lagoon connected to the Mediterranean Seato a brackish/freshwater environment. Sebkhas El-Guettiate and Dreîaa have developed from marine bays to dry salt flats. Lac Ichkeul is eutrophied and has become brackish since the time of Gauthier. We also describe a new species, Psychrodromus tunisicus n. sp., and present a determination key for the genus. The finding of a species of the genus Psychrodromus is the first report of this genus inNorth Africa.